Maternal Behavior of Laboratory-born, Individually Reared Long-tailed Macaques (Macaca fascicularis) - Tsuchida, Junko (American Association for Laboratory Animal Science, 2008)
To investigate maternal behavior in laboratory-born, individually reared monkeys, we carried out a statistical analysis of 896 long-tailed macaques (Macaca fascicularis) based on breeding records of the Tsukuba Primate Research Center (National Institute of Biomedical Innovation, Ibaraki, Japan). Data were obtained from 3266 cases of normal delivery between 1982 and 2004. In each case, maternal behavior was classified as either adequate or inadequate. We examined the effects of parity and the sex of the infant on maternal behavior. We also investigated the similarity of maternal behavior between mothers and their daughters and the effect of quality of maternal care received in infancy on maternal behavior as an adult. The results showed that only the mother's number of deliveries had a significant effect on maternal behavior. The greatest improvement of maternal behavior was observed at second delivery, and the incidence of improvement kept being above 0 thereafter. Our results suggest that, as reported previously, parity is an important factor in the adequacy of maternal behavior in individually reared monkeys.